Optimizing chillies (Capsicum annum L.) germination rate and early seedling performance through nutrient seed priming with potassium nitrate and zinc oxide - Maphalaphathwa, Mufunwa; Nciizah, Adornis Dakarai (Frontiers in Plant Science, 2025)
Chillies are an economically important crop in South Africa, with increasing demand for both domestic consumption and export. However, smallholder production remains low due to environmental and economic constraints, particularly poor seed germination and weak seedling vigor, which limit fruit quality and yield. Agrotechnological developments, such as seed priming, which is a crucial pre-sowing treatment, can enhance crop establishment and ensure yield consistency. Seed priming, particularly nutrient seed priming (NSP), enhances germination and seedling establishment in various crop species, including Capsicum annum L. Although nutrient seed priming (NSP) has improved germination in various crops, species-specific optimization of priming duration and concentration is essential. Currently, no standardized priming protocols exist for chillies in South Africa, necessitating further research, An 8 x 3 factorial experiment was conducted under laboratory and glasshouse conditions to evaluate the effects of eight priming treatments (20 mg/L ZnO, 10 mg/L ZnO, 15 mg/L ZnO, 5 mg/L ZnO, 10 g/L KNO3, 5 g/L KNO3, 2.5 g/L KNO3, and H2O) at three priming durations (6, 12, and 24 h) on chilli seed germination and seedling growth. ZnO and KNO3 significantly (p< 0.05) influenced germination and early growth parameters. Under laboratory conditions, priming with 20 mg/L ZnO resulted in the highest germination rates, with optimal priming durations of 12 h for ZnO and 24 h for KNO3. In the glasshouse, priming with 20 mg/L ZnO for 6 h improved seedling vigor, including shoot height, root length, and biomass accumulation. These findings indicate that ZnO priming, particularly at 20 mg/L for 6 h, is a promising strategy to enhance chilli seedling establishment under South African conditions, potentially improving productivity for smallholder farmers. The results showed that the optimal combination of NSP varies with specific germination indices. Under laboratory conditions, priming with 20 mg/L ZnO led to higher germination rates than KNO3 with optimal priming durations of 24 hours for KNO3 and 12 hours for ZnO. In the glasshouse, priming seeds with 20 mg/L ZnO for 6 hours produced the best results across most indices demonstrating that priming with ZnO in particular, could be an effective strategy for enhancing early growth and vigor in chillies seedlings.